Bilateral adrenal pathology: Conn syndrome and autonomous cortisol secretion - Hradova , Diana; Yuzvenko , Violetta (The Ukrainian Scientific Medical Youth Journal, 2023)
this case report presents the route of a patient with bilateral adrenal pathology and severe complaints, who where admitted to the Ukrainian Scientific and Practical Center for Endocrine Surgery, Transplantation of Endocrine Organs and Tissues of MoH of Ukraine as scheduled. The selective blood sampling from adrenal veins, which was performed at the Center, in patient with bilateral adrenal pathology, is analyzed. This method is the gold standard of diagnosis, which allows to choose the optimal method of treatment for such patients.